2020
DOI: 10.1017/s0029665120003067
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrittion among Dutch children? Results of the Dutch national food consumption survey 2012–2016

Abstract: AbstractIntroduction:An adequate and balanced intake of energy and nutrients is important for growth of children and prevention of diseases. The aim of this study was to get insight in the prevalence of low and high intakes of micronutrients and its association with overweight among Dutch children. This insight can contribute to the development of policy on healthy diet and specific nutritional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
200
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(229 citation statements)
references
References 0 publications
26
200
1
2
Order By: Relevance
“…The mean dietary Mg intake we report (305 ± 46 mg/day) was somewhat lower than the median Mg intake in the general Dutch population, which is around 350 mg/day [ 22 ], but was comparable to median Mg intake of population studies in the U.S. (308 mg/day) [ 4 ]. We found that in the Dutch population, cereals, dairy, and coffee intake were the largest contributors to total Mg intake, at 22%, 14%, and 9% respectively.…”
Section: Discussioncontrasting
confidence: 38%
“…The mean dietary Mg intake we report (305 ± 46 mg/day) was somewhat lower than the median Mg intake in the general Dutch population, which is around 350 mg/day [ 22 ], but was comparable to median Mg intake of population studies in the U.S. (308 mg/day) [ 4 ]. We found that in the Dutch population, cereals, dairy, and coffee intake were the largest contributors to total Mg intake, at 22%, 14%, and 9% respectively.…”
Section: Discussioncontrasting
confidence: 38%
“…At the same time, the median of dietary intake was also very low, as it was 1.9 µg (0.2–8.0 µg) for 3-day dietary record, 3.3 µg (1.1–10.6 µg) for Cro-VIDEO-FFQ1 and 3.6 µg (1.4–7.8 µg) for Cro-VIDEO-FFQ2. The observed intake level may be compared with the level reported by EFSA for other countries [ 3 ] and it may be stated, that the level observed for young women in Croatia is comparable with the level stated for young women in Germany (2.0–2.6 µg) [ 50 ], Austria (2.1–3.3 µg) [ 51 ], Ireland (2.4 µg) [ 52 ], Netherlands (2.6 µg) [ 53 ] and Denmark (2.6–2.8 µg) [ 54 ].…”
Section: Discussionmentioning
confidence: 59%
“…The number of spikes in the time scan is directly proportional to the number of particles in the sample. The signal height of the peaks is directly proportional to the particle’s mass from which the equivalent spherical particle size is calculated [ 22 , 23 ]. c The calculated number-based particle size distribution (left axis and dark colours) and the calculated mass-based particle size distribution (right axis and light colours).…”
Section: Resultsmentioning
confidence: 99%
“…While there is no information about their diets, it is known that all persons involved are of Caucasian ethnicity except one who was of Asian ethnicity. All have lived in the Netherlands their entire life and it is therefore assumed that most followed a Dutch diet [ 22 ]. Of the 15 persons involved, 2 received titanium implants during their lifetime.…”
Section: Methodsmentioning
confidence: 99%